MODERASI FREE CASH FLOW TERHADAP FAKTOR-FAKTOR YANG MEMENGARUHI EARNINGS RESPONSE COEFFICIENT - Filbert Nathaniel; Rizka Indri Arfianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2019)
Financial statements are the information used by investors and stakeholders for consideration of decision making. One of the important information is earnings. Quality earnings information can be relied on by users to predict the company's performance in the future. Earnings response coefficient (ERC) is a variable that measures the level of market reaction to the publication of earnings. Increasingly high market reaction means the earnings are qualified. But many other pieces of information that affect ERC, the increase in earnings is not always followed by an increase in market reaction. In this research, the other pieces of information are leverage, earnings persistence, size, and growth with free cash flow (FCF) as a moderating size and growth. The Sample of this research is 31 LQ45 companies which are listed in the IDX period 2015-2017. Sampling techniques to be used are the Non-Probability Sampling technique with Judgement Sampling Method. The data analysis method which is used in this research is the Structural Equation Model in WarpPls 5.0. The results' inner model and overall fittest are fulfilled. The conclusion showed that the leverage, size, and growth hasn’t affected the ERC, and free cash flow is not able to strengthen influence growth on ERC. However, earnings persistence has affected positively on ERC and free cash flow can strengthen influence size on ERC.Keywords: Earnings Response Coefficient, Leverage, Earnings Persistence, Size, Growth, Free Cash Flow